2013
DOI: 10.1007/s00455-013-9452-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Dose–Volume Correlates for Structures Related to Late Swallowing Disturbances After Radiotherapy for Head and Neck Cancer

Abstract: Mean dose to the pharyngeal constrictor muscles appeared to be the most important dosimetric predictor of late swallowing disturbances. Suggested dose-volume correlates require validation in prospective well-designed clinical trials, applying appropriate statistical methods that would account for possible interfering factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…Examination of dose-volume correlates for the DARS [54] have also revealed that the mean dose to the pharyngeal constrictor muscles was the most important dosimetric predictor of late swallowing complications (>3 months post-(C)RT). Whilst the notion of the general resistance of skeletal muscle to RT is well-accepted [55], it has been postulated that the PHYSIOLOGICAL SWALLOWING DEFICITS FOLLOWING (C)RT FOR HNC 13 pharyngeal constrictor and laryngeal adductor muscles and epiglottic walls, which are situated in close proximity to the submucosa, may be secondarily affected by the acute radiation-induced inflammatory response of these mucosal layers, culminating in the loss of elasticity and therefore dysfunction of the laryngeal and oropharyngeal musculature [32,56].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Examination of dose-volume correlates for the DARS [54] have also revealed that the mean dose to the pharyngeal constrictor muscles was the most important dosimetric predictor of late swallowing complications (>3 months post-(C)RT). Whilst the notion of the general resistance of skeletal muscle to RT is well-accepted [55], it has been postulated that the PHYSIOLOGICAL SWALLOWING DEFICITS FOLLOWING (C)RT FOR HNC 13 pharyngeal constrictor and laryngeal adductor muscles and epiglottic walls, which are situated in close proximity to the submucosa, may be secondarily affected by the acute radiation-induced inflammatory response of these mucosal layers, culminating in the loss of elasticity and therefore dysfunction of the laryngeal and oropharyngeal musculature [32,56].…”
Section: Discussionmentioning
confidence: 98%
“…Eisbruch et al [32] were the first to postulate a set of dysphagia/aspiration-related structures (DARS) -deglutitive structures whose damage was deemed likely to cause dysphagia and aspiration, as observed on videofluroscopy, and demonstrated radiation-induced structural changes in posttreatment CT scans. Recent review papers have reported these DARS to include the: superior, middle and inferior pharyngeal constrictors, glottic and supraglottic larynx and its adductor muscles, upper esophageal sphincter and mucosal/submucosal surfaces of the BOT [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews have reported on the impact of dose to dysphagia and aspiration structures on dysphagia. This evidence is outdated due to new literature in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Severe swallowing disturbances and xerostomia lead to nutritional deficiency, weight loss, prolonged parenteral or gastric tube feeding, higher risk for aspiration, anxiety and depression, and diminished quality of life. Depending on treatment (radiotherapy alone or combined with chemotherapy), treated volume, radiation dose, fractionation, and overall treatment duration, the incidence of late symptomatic disturbances was reported as high as 50 % [25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 98%